2010
DOI: 10.1007/s00125-010-1887-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hyperglycaemia causes non-reversible changes in arterial gene expression in a fully ‘switchable’ in vivo mouse model of diabetes

Abstract: Aims/hypothesis Irreversible arterial damage due to early effects of hypo-or hyperglycaemia could account for the limited success of glucose-lowering treatments in preventing cardiovascular disease (CVD) events. We hypothesised that even brief hypo-or hyperglycaemia could adversely affect arterial gene expression and that these changes, moreover, might not be fully reversible. Methods By controlled activation of a 'switchable' c-Myc transgene in beta cells, adult pIns-c-MycER TAM mice were rendered transiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…These genes were involved in atherogenic processes, including inflammation and arterial calcification. Although the expression of many genes returned to its initial level after 3 months, in one in four genes, recovery was not observed [160]. These data indicate that non-physiological glucose fluctuations may have a prolonged effect on gene expression.…”
Section: Gene Expressionmentioning
confidence: 74%
“…These genes were involved in atherogenic processes, including inflammation and arterial calcification. Although the expression of many genes returned to its initial level after 3 months, in one in four genes, recovery was not observed [160]. These data indicate that non-physiological glucose fluctuations may have a prolonged effect on gene expression.…”
Section: Gene Expressionmentioning
confidence: 74%
“…Moreover, it was suggested that brief hypoglycaemia could irreversibly affect atrial gene expression favouring CV risk [83]. …”
Section: Resultsmentioning
confidence: 99%
“…Other studies demonstrate that hyperglycemia causes changes in aortic gene expression, including in genes involved in inflammation and calcification, in a non-atherosclerotic mouse model. 60 Another approach to evaluate the role of increased glucose metabolism in SMCs is to overexpress the glucose transporter GLUT1. Targeted overexpression of GLUT1 in SMCs leads to increased vascular inflammation, as assessed by an increased number of neutrophils and increased CCL2 levels in a balloon injury model in non-atherosclerotic mice.…”
Section: First Question: Which Cell Type Involved In Atherosclerosis mentioning
confidence: 99%